2016
DOI: 10.5530/pj.2016.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-acute Toxicity study of Aqueous extracts of Canscora heteroclita (L) Gilg in Rodents

Abstract: Background: Canscora heteroclita (C. heteroclita) being used in the Ayurvedic system of medicine in India for the treatment of various diseases. No systematic toxicity study for this plant was described. Objective: The present study was undertaken to assess the safe use of this plant in traditional practice. Materials and Methods: The acute oral toxicity study of aqueous extract of Canscora heteroclita (AECH) was carried out as per the OECD guidelines 423 in mice and the sub-acute toxicity was carried out at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Normal food and water consumption of animals support the gain in the body weight of animals throughout the study period. Similar findings were also observed in this study as no significant reduction in the body weight was noted in any group of the animals 21 . Moreover no significant difference was observed in relative weight of any organ (viz.…”
Section: Discussionsupporting
confidence: 92%
“…Normal food and water consumption of animals support the gain in the body weight of animals throughout the study period. Similar findings were also observed in this study as no significant reduction in the body weight was noted in any group of the animals 21 . Moreover no significant difference was observed in relative weight of any organ (viz.…”
Section: Discussionsupporting
confidence: 92%
“…Although acute toxicity helps to determine the toxicity nature of substances, it is important to assess subacute oral toxicity profile because it helps to evaluate the morphological and physiological changes in organs after repeated administration [33, 34]. In oral toxicity assessment the body weight change is sensitive and indicative marker for toxicity sign [35]. No significant changes in the body weight were observed in treated mice compared to untreated group after 21 days administration of L. angustifolia EO.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that the extract BERM, may contains some nutritive substances which led the animals to be active. On the contrary, the results obtained by [33] clearly suggested that there is an increase in the body weight of the animals was observed. In terms of organ weight ratio, the results found to be normal and all within the range.…”
Section: Discussionmentioning
confidence: 82%